2023
DOI: 10.1177/15589250231181701
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of structural characteristics, dimensional change in washing, non-creasing properties and air permeability of Swiss double piqué flax knit fabrics

Nadiia P Bukhonka

Abstract: The structural characteristics, dimensional change after four washing cycles, non-creasing properties and air permeability of Swiss double piqué knitted fabrics from cotton/flax (70% cotton, 30% flax), PAN/flax (70% PAN, 30% flax) and 100% flax yarns have been investigated. These knitted fabric samples of varying densities were produced on a 10 -gauge circular knitting machine. The results of investigation showed that the structural characteristics, dimensional change in washing, non-creasing properties and ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…These issues have been addressed by scientists M.S. Bukhonka (2023) studied the effect of mixing natural and synthetic fibres on improving the consumer properties of the resulting materials, which is carried out to achieve a high level of comfort and functionality of finished textile and knitted products.…”
Section: Discussionmentioning
confidence: 99%
“…These issues have been addressed by scientists M.S. Bukhonka (2023) studied the effect of mixing natural and synthetic fibres on improving the consumer properties of the resulting materials, which is carried out to achieve a high level of comfort and functionality of finished textile and knitted products.…”
Section: Discussionmentioning
confidence: 99%
“…Stitches such as knit, miss, and tuck can lead to variations in fabric properties. [3][4][5] Each knit structure has its own distinct characteristics, and the choice of a particular structure depends on the desired properties and intended application of the fabric. [6][7][8][9] Choosing the appropriate knit structure for cotton knitted fabrics becomes crucial to effectively enhance properties like smoothness of the fabric surface, air permeability, heat transmittance, and hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%
“…22 The width repeat of the miss stitches influences the dimensional changes of the single weft jacquard knitted fabrics. 23 Investigation of the influence of the type of relaxations such as knitting&dry relaxation, dye&dry relaxations, dye&wash relaxations for the single jersey, 1 × 1 rib and interlock knit structures on the dimensional properties of cotton knitted fabrics showed that the shape of the loop in the fabric and loop length of yarn are the main factors which are responsible for the dimensional properties. 24 Knitted garments experience various stresses and loads throughout their use, which can vary in magnitude, direction, and duration.…”
Section: Introductionmentioning
confidence: 99%
“…It has been stated that linen blended fabrics increase cotton UV protection factor and color efficiency, reduce burst strength and allow more moisture absorption (Sanad, 2011). In another study, Bukhonka (2023), conducted a study on the dimensional changes and air permeability of Swiss double pique knitted fabrics produced using PAN/linen, cotton/linen and pure linen. It was determined that there was more dimensional change in knitted fabrics made from cotton/linen and pure linen yarns and that the knitted fabric made from pure linen yarn had the highest air permeability (Bukhonka, 2023).…”
Section: Introductionmentioning
confidence: 99%